2001
DOI: 10.1523/jneurosci.21-15-05752.2001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Properties of the Trigeminal Somatosensory System in Rats Performing Whisker-Dependent Tactile Discriminations

Abstract: To address several fundamental questions regarding how multiwhisker tactile stimuli are integrated and processed by the trigeminal somatosensory system, a novel behavioral task was developed that required rats to discriminate the width of either a wide or narrow aperture using only their large mystacial vibrissae. Rats quickly acquired this task and could accurately discriminate between apertures of very similar width. Accurate discriminations required a large number of intact facial whiskers. Systematic remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
238
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(252 citation statements)
references
References 34 publications
(59 reference statements)
12
238
2
Order By: Relevance
“…Freely moving rodents can discriminate the roughness of textures (Guić-Robles et al, 1989;Carvell and Simons, 1990;von Heimendahl et al, 2007) and the widths of apertures (Krupa et al, 2001). Rodents also accurately judge the distances to platforms ("gap crossing") (Hutson and Masterton, 1986;Celikel and Sakmann, 2007) and the relative distance of two objects (Knutsen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freely moving rodents can discriminate the roughness of textures (Guić-Robles et al, 1989;Carvell and Simons, 1990;von Heimendahl et al, 2007) and the widths of apertures (Krupa et al, 2001). Rodents also accurately judge the distances to platforms ("gap crossing") (Hutson and Masterton, 1986;Celikel and Sakmann, 2007) and the relative distance of two objects (Knutsen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Rats also exhibit asymmetric whisking (Mitchinson et al, 2007;Towal and Hartmann, 2008) and irregular whisker movements during a horizontal object localization task (Knutsen et al, 2006). Active whisking is not required to solve all spatial tasks: rats can determine the width of an aperture after sectioning of the facial nerve (Krupa et al, 2001). The whisking strategies used by rodents to solve spatial localization problems are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical properties of whisker stimulation in rats have been assessed early on (Vincent, 1912;Schiffman et al, 1970). It has been shown that rats are capable of amazingly fine discriminations of surfaces (GuicRobles et al, 1989;Carvell and Simons, 1990) and apertures (Krupa et al, 2001), and that discrimination of textures and object forms are optimized by active scanning movements (Carvell and Simons, 1995;Harvey et al, 2001;Prigg et al, 2002). Finally, the detectability of 1-3°whisker deflections applied by a sinusoidally modulated air stream (at 0.1-32 Hz) in mobile rats was demonstrated in the only study so far that attempted to use parameterized whisker deflections (Hutson and Masterton, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Designing such tasks is challenging because of the difficulty of applying spatiotemporally precise stimuli to awake behaving rats while precluding nonvibrissal stimulus sources (such as cutaneous receptors or the small perioral sinus hairs) under conditions which allow for the assessment of psychophysical parameters. Psychophysical studies conducted so far mostly used nonrestrained, freely moving rats sampling stimuli by using their own body and whisker movements Simons, 1990, 1995;Harvey et al, 2001;Krupa et al, 2001). Hutson and Masterton (1986) are the only investigators so far who attempted to quantify psychophysical detection thresholds with varying kinematic deflection parameters; however, rats in that study were free to move their head, and control of whisker deflection generated by air streams did not reach the level of stimulus control deemed necessary: micrometer precision at a millisecond time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Such navigation is heavily dependent on the use of facial vibrissae, which are extremely sensitive tactile organs used as both highresolution tactile discriminators (2,3) and distance detectors (4,5). During exploration, the vibrissae are bilaterally swept against objects and obstacles to gather accurate information about the animal's close surroundings (2)(3)(4)(5).…”
mentioning
confidence: 99%